Effect of surface treatment on the shear bond strength of a resin-based cement to porcelain - Nagayassu, Marcos Paulo [UNESP]; Shintome, Luciana Keiko [UNESP]; Uemura, Eduardo Shigueyuki [UNESP]; Araújo, José Eduardo Junho De [UNESP] (Fundação Odontológica de Ribeirão Preto, 2006)
The purpose of this in vitro study was to evaluate the effect of different surface treatments on the shear bond strength of a resin-based cement to porcelain. Sixty pairs of 50% aluminous porcelain discs were fabricated. In each pair, one disc measured 6 mm in diameter X 3 mm thickness (A) and the other measured 3 mm in diameter X 3mm thickness (B). The specimens were randomly assigned to 6 groups (n=10 pairs of discs), according to the surface treatment: etching with 10% hydrofluoric acid for 2 or 4min (G1 and G2); 50-µm particle aluminum oxide sandblasting for 5 s (G3); sandblasting followed by etching for 2 or 4min (G4 and G5) and control - no treatment (G6). A silane agent was applied to the treated surface of both discs of each pair. Bistite II DC dual-cure resin cement was applied and the B discs were bonded to their respective A discs. Specimens were stored in distilled water at 37ºC for 24 h and were tested in shear strength at a crosshead speed of 2 mm/min. Means in MPa were: G1: 14.21 ± 4.68; G2: 8.92 ± 3.02; G3: 10.04 ± 2.37; G4: 12.74 ± 5.15; G5: 10.99 ± 3.35; G6: 6.09 ± 1.84. Data were compared by one-way ANOVA and Tukey's test at 5% significance level. Bond strength recorded after 2-min acid etching was significantly higher than 4-min etching (p<0.05) and control (p<0.05), but did not differ significantlyfrom sandblasting alone (p>0.05) or followed by etching for 2 or 4 min (p>0.05). Within the limitations of an in vitro study, it may be concluded that 2-min hydrofluoric acid etching produced a favorable micromechanical retention that enhanced resin cement bond strength to porcelain.

O objetivo deste estudo in vitro foi avaliar o efeito de diferentes tratamentos de superfície na resistência ao cisalhamento da união entre porcelana e cimento resinoso. Foram confeccionados sessenta pares de discos de porcelana aluminizada a 50%, de 6 mm de diâmetro por 3 mm de espessura (A) e 3 mm de diâmetro por 3 mm de espessura (B). Os espécimes foram divididos aleatoriamente em 6 grupos (n=10 pares), de acordo com os tratamentos de superfície: condicionamento com ácido fluorídrico por 2 e 4 min (G1 e G2), jateamento com óxido de alumínio (50 µm) por 5 s (G3), jateamento seguido de ácido fluorídrico por 2 e 4 min (G4 e G5) e controle (G6). Em seguida, foi aplicado silano na superfície tratada de ambos os discos, e os discos B foram cimentados sobre os respectivos discos A, utilizando o cimento resinoso dual Bistite II DC. Os espécimes foram armazenados em água destilada a 37ºC por 24 h, para posterior teste de cisalhamento em máquina de ensaio universal. As médias em MPa foram: G1: 14,21 ± 4,68; G2: 8,92 ± 3,02; G3: 10,04 ± 2.37; G4: 12,74 ± 5,15; G5: 10,99 ± 3,35; G6: 6,09 ± 1,84. Os dados foram submetidos à análise de variância a um critério e teste de Tukey (p<0,05). O condicionamento ácido por 2 min apresentou resultados significantemente superiores ao condicionamento por 4 min (p<0,05) e ao grupo controle (p<0,05), porém não diferiu estatisticamente do jateamento, associado ou não ao ácido fluorídrico por 2 ou 4 min (p>0,05). Dentro das limitações de um estudo in vitro, conclui-se que o condicionamento com ácido fluorídrico por 2 min produziu uma retenção micromecânica favorável, que aumentou a resistência de união entre o cimento resinoso e a porcelana.
Keywords: porcelain; resin-based cement; surface treatments; cementation